Studies on the Status of some Species of Rattans (Calamus spp.) in the forests of Western Ghats of Karnataka, India - Bhat, P. Rama; Soorya Prakash Shenoy, H.; Kaveriappa, K. M. (Indian Forester, 2009)
The rattans of Peninsular India belong to only one genus namely Calamus and 21 species. Twenty species occurring in Western Ghats forests are reported here. The status of C. delessertianus and C. rheedei is uncertain while 15 species are endemic to Western Ghats. Among the five states falling within the Western Ghats, Karnataka has the maximum 13 Calamus species, of which 11 were endemic to the Western Ghats. Three species namely, C. lacciferus, C. lakshmanae and C. prasinus were restricted only to Karnataka region of the Western Ghats. Among the 13 species of Calamus occurring in Karnataka, 12 were found in Kodagu District. Studies were undertaken to determine the status of rattans in some canerich forests of Kodagu, Dakshina Kannada and Uttara Kannada districts of Karnataka by belt transect method. The study has revealed that Sampaje, Karike and Makut in Kodagu District, Subramanya and Charmadi in Dakshina Kannada District and Anantavadi (Honnavar) in Uttara Kannada District were rich in some species of rattans including those endemic to the Western Ghats. The population of C. lakshmanae and C. prasinus (restricted only to Karnataka) was high in Sampaje and Karike forest respectively, however, C. stoloniferus (restricted to Karnataka and Maharashtra) was very high in Makut forest of Kodagu District. In Dakshina Kannada District C. nagabettai was well distributed in about 25 km radius around Subramanya, while Charmadi area has a rich population of C. thwaitesii and fairly good representations of C. prasinus, C. pseudotenuis and C. nagabettai. The population density of C. karnatakensis (restricted to Karnataka and Goa) was very high in Anantavadi forests near Honnavar.